Yield and grape must quality of the IAC 138-22 ‘Máximo’ submitted to canopy management - Hernandes, José Luiz; Pedro Júnior, Mário José (Revista Ceres, 2025)
Grape cultivar IAC 138-22 ‘Máximo’ grafted on IAC 766 ‘Campinas’ and IAC 572 ‘Jales’ rootstocks and trained in upright trellis was evaluated during consecutive summer and winter growing seasons for comparison different canopy management: a) branch thinning: comparison between one branch and two branches per spur and b) branch tipping: comparison between low and high upright trellis. The results obtained of the phytotechnical and physicochemical grape must characteristics allowed to confirm that there was no significant difference between rootstocks regarding branch thinning intensity and upright trellis height. The largest effect observed in canopy management was for yield values promoted by branch thinning. No effect was observed in the grape must physicochemical characteristics when the different treatments were compared in the same growing season. Regarding to the upright trellis height, larger values of soluble solids were obtained for the high trellis than in the low trellis. Winter growing season resulted in lower values of yield and greater values of total soluble solids and titratable acidity than in the summer growing season.